1978
DOI: 10.1007/bf01880679
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic aspects of aplastic anemia in pregnancy

Abstract: Our resent experience on six cases of aplastic anemia complicated with pregnancy is described. In addition, 43 similar cases were collected from the literature and reviewed to analyze some prognostic aspects of this relatively rare but potentially serious complication. Clinical and hematological data were treated to extract some clinically meaningful factors in relation to the success and failure of pregnancy. Among initial hematological parameters, no significant difference was found between successful and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 20 publications
(13 reference statements)
0
3
1
1
Order By: Relevance
“…It has been suggested that the outcome of pregnancy and maternal survival were better in women who had AA before pregnancy as compared to those in whom it developed during pregnancy [8], [20]. However, our study demonstrated that there are no differences between the 2 groups with regards to severity and postpartum condition.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…It has been suggested that the outcome of pregnancy and maternal survival were better in women who had AA before pregnancy as compared to those in whom it developed during pregnancy [8], [20]. However, our study demonstrated that there are no differences between the 2 groups with regards to severity and postpartum condition.…”
Section: Discussioncontrasting
confidence: 81%
“…Deka argued that maternal and fetal outcome is poor in severe AA [16]. On the contrary, Suda reported no hematologic differences between successful and unsuccessful groups [8]. Those results are conflicting not only because they involved small sample sizes, but also because they applied the same prognostic factor as overall AA without special consideration of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aplastic anaemia occurring in pregnancy is an uncommon event. Although previously associated with an extremely poor prognosis (Fleming 1973), cases reported since 1970 have been associated with an overall maternal survival of 80% (Suda et al 1978). The survival rates, however, are proportional to the severity of the aplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Die aplastische Anämie als klinische Entität wurde erstmals 1888 von Ehrlich beschrieben, bemerkenswerterweise ebenfalls bei einer Schwangeren (6). Seither sind die Meinungen darüber geteilt, ob eine kausale Beziehung zwischen Schwangerschaft und aplastischer Anämie besteht oder ob es sich dabei nur um eine zufällige Koinzidenz handelt (5,7,11,14). Für eine kausale Beziehung sprechen Einzelbeobachtungen, bei denen sich nach Beendigung der Schwanger-schaft das Blutbild wieder normalisierte (10,11).…”
Section: Diskussionunclassified